Native arbuscular mycorrhizal fungi promote Plukenetia volubilis growth and decrease the infection levels of Meloidogyne incognita - Corazon-Guivin, M.A.; del Aguila, S.R.; Correa, R.X.; Cordova-Sinarahua, D.; Maia, L.C.; Alves da Silva, D.K.; da Silva, G.A.; Lopez-Garcia, A.; Coyne, D.; Oehl, F. (MDPI, 2024)
The use of arbuscular mycorrhizal fungi (AMF) offers promising benefits to agriculture in the Amazon regions, where soils are characteristically acidic and nutrient-poor. The purpose of this research was to investigate the potential effects of two recently described species of AMF (Nanoglomus plukenetiae and Rhizoglomus variabile) native to the Peruvian Amazon for improving the plant growth of Plukenetia volubilis (inka nut or sacha inchi) and protecting the roots against soil pathogens. Two assays were simultaneously conducted under greenhouse conditions in Peru. The first focused on evaluating the biofertilizer effect of AMF inoculation, while the second examined the bioprotective effect against the root knot nematode, Meloidogyne incognita. Overall, the results showed that AMF inoculation of P. volubilis seedlings positively improved their development, particularly their biomass, height, and the leaf nutrient contents. When seedlings were exposed to M. incognita, plant growth was also noticeably higher for AMF-inoculated plants than those without AMF inoculation. Nematode reproduction was significantly suppressed by the presence of AMF, in particular R. variabile, and especially when inoculated prior to nematode exposure. The dual AMF inoculation did not necessarily lead to improved crop growth but notably improved P and K leaf contents. The findings provide strong justification for the development of products based on AMF as agro-inputs to catalyze nutrient use and uptake and protect crops against pests and diseases, especially those that are locally adapted to local crops and cropping conditions.